Initial COVID-19 Transmissibility and Three Gaseous Air Pollutants (NO2, SO2, and CO): A Nationwide Ecological Study in China - Ran, Jinjun; Zhao, Shi; Han, Lefei; Peng, Zhihang; Wang, Maggie H.; Qiu, Yulan; He, Daihai (Frontiers in Medicine, 2020)
Recently, the effects of ambient pollutants, e.g., NO2, SO2, and CO, on the transmission of coronavirus diseases 2019 caught wide attention. In this study, we conducted an ecological study to examine their effects in the early phase of the pandemic (from December 2019 to February 2020) in China. We found that the associations between the average concentration of NO2, SO2, and CO and the COVID-19 transmissibility are not statistically clear. We discuss the possible reasons.